OER A Field Guide for Academic Librarians - Wesolek, Andrew; Lashley, Jonathan; Langley, Anne (Open textbook library., 2018)
We intend this book to act as a guide writ large for would-be champions of OER, that anyone—called to action by the example set by our chapter authors—might serve as guides themselves. The following chapters tap into the deep experience of practitioners who represent a meaningful cross section of higher education institutions in North America. It is our hope that the examples and discussions presented by our authors will facilitate connections among practitioners, foster the development of best practices for OER adoption and creation, and more importantly, lay a foundation for novel, educational excellence.